Human Teeth - Key Skills and Clinical Illustrations 2020
DOI: 10.5772/intechopen.84151
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Root Canal System of Maxillary and Mandibular Molars

Abstract: The root canal system is complicated and has many anatomical variations among different populations. It is so important to understand the morphology of root canal system before any endodontic procedure, since the lack of knowledge of root canal system could lead to missing the additional root canals which causes failure of endodontic treatment. The study of root canal anatomy was carried out by many researchers and among different populations using various techniques. The presence of additional root canals was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
0
9
1
Order By: Relevance
“…The current work reported two canals to be present in 73.6% mandibular third molars. This incidence was considerably higher than the studies reported in a group of U.S inhabitants (16.7%), Croatians (6%), Jordanians (38.6%) and 9,16,23,24 Russians (40.9%).…”
Section: Discussioncontrasting
confidence: 62%
“…The current work reported two canals to be present in 73.6% mandibular third molars. This incidence was considerably higher than the studies reported in a group of U.S inhabitants (16.7%), Croatians (6%), Jordanians (38.6%) and 9,16,23,24 Russians (40.9%).…”
Section: Discussioncontrasting
confidence: 62%
“…Further studies investigating the root canal morphology of permanent maxillary molars are needed because of the complexity and different anatomical configurations of these teeth [ 3 , 4 ] Knowledge of these configurations is essential to identify and treat additional canals and to increase the chances of successful endodontic treatment [ 4 , 8 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Improvements in endodontic treatment have been achieved over the past decades by the development of new materials, techniques, and devices in order to increase success rates [ 2 ]. However, the success of this treatment depends on accurate knowledge about the morphology of root canals, which is very complex due to the splitting and union of canals during their trajectory [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations